Demographic, Economic and Social Effects of International Migration - example of selected countries - Bilgin, Başak; Miskolczi, Martina; Hon, Filip; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
International migration has become a significant phenomenon in today's globalized world, with profound demographic, economic, and social impacts on both sending and receiving countries. This master thesis investigates the effects of international migration in three diverse countries: the Netherlands, Turkey, and Canada. The study employs an overview to the theories of migration, studies the diverse effects of migration and uses official data of the selected countries to comprehensively examine the multifaceted consequences of international migration. Demographically, the thesis analyzes changes in population dynamics, including migration patterns, fertility rates, and aging populations. Economically, the thesis examines the impact of immigration on remittances, investment, brain drain, and shadow economy. Socially, the thesis explores the effects of international migration in challenges and opportunities for migrants' integration into the host societies, social cohesion, cultural diversity, discrimination, and religious structure. The findings reveal that international migration has significant demographic, economic, and social effects in the Netherlands, Turkey, and Canada, albeit with unique country-specific variations. While migration contributes to population growth and labor force dynamics in all three countries, it also presents challenges such as cultural integration, discrimination, and social disparities. However, it also brings opportunities for economic development, innovation, and cultural enrichment. The thesis argues that understanding the complex interplay between demographic, economic, and social factors is crucial for formulating effective policies and strategies to manage the impacts of international migration in diverse countries.
Vedoucí práce: Martina Miskolczi
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: data analysis and modeling [obor dipl. práce]; diplomové práce; master's theses